Iconoclasm from Antiquity to Modernity - Kolrud, Kristine (Taylor and Francis, 2014)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of Illustrations -- Notes on Contributors -- Acknowledgements -- 1 Introduction - Whose Iconoclasm? -- 2 Disabling Demonic Images: Regional Diversity in Ancient Iconoclasts' Motives and Targets -- 3 Presence and the Image Controversies in the Third and Fourth Centuries AD -- 4 Defacement and Replacement as Political Strategies in Ancient and Byzantine Ruler Images -- 5 Byzantine Iconoclasm: Ideology and Quest for Power -- 6 Neither Iconoclasm nor Iconodulia: The Carolingian Via Media